Physical education and physical culture in the Coloured community of the Western Cape, 1837-1966 - Cleophas, Francois Johannes (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Sport Science))—University of Stellenbosch, 2009.